Acute diarrhea, feeding and diet: Is caregivers approach out of rationale? - Jaigam Abbas; Dinesh Chandra Pandey; Ashish Verma (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: The feeding and or diet in infants and young children with acute diarrhea is an unresolved health problem at the community level. Despite recommendations from several bodies, including the World Health Organization that feeding should be continued during diarrhea. The practice of withholding balance diet or breast feeding during the acute diarrhea is still prevalent and it is one of the major public health issue, and this may lead to development of malnutrition, which may further prevent recovery from diarrhea. Aims & objectives: We aimedtoassess caregivers approach towards feeding and or diet in children with acute diarrhea. Subjects and Methods: This was aqualitative, cross-sectional, hospital based survey carried among caregivers of infants and young children aged 6 months - 24 months of either sex with acute diarrhea from April 2017 to December 2018. Results: the attitude of caregivers towards feeding and or diet in children with acute diarrhea was not appropriate, which may lead to bad clinical outcomes in terms of recovery from diarrhea and further may increase the burden of malnutrition. Conclusion: There was gross irrational approach of caregivers found towards feeding and or diet in younger children with acute diarrhea and to prevent myths towards feeding and or diet, the health awareness towards basic nutrition is need of era and to be maintained at the highest level in the community